Cryo-EM structures of the autoinhibited E. coli ATP synthase in three rotational states - Sobti, Meghna (2018)
A molecular model that provides a framework for interpreting the wealth of functional information obtained on the E. coli F-ATP synthase has been generated using cryo-electron microscopy. Three different states that relate to rotation of the enzyme were observed, with the central stalk’s ε subunit in an extended autoinhibitory conformation in all three states. The Fo motor comprises of seven transmembrane helices and a decameric c-ring and invaginations on either side of the membrane indicate the entry and exit channels for protons. The proton translocating subunit contains near parallel helices inclined by ~30° to the membrane, a feature now synonymous with rotary ATPases. For the first time in this rotary ATPase subtype, the peripheral stalk is resolved over its entire length of the complex, revealing the F1 attachment points and a coiled-coil that bifurcates toward the membrane with its helices separating to embrace subunit a from two sides.